Different Materials for Plugging a Dehiscent Superior Semicircular Canal: A Comparative Histologic Study Using a Gerbil Model. Issue 5 (June 2019) - Kwok, Pingling; Gleich, Otto; Spruss, Thilo; Strutz, Jürgen
Abstract : Hypothesis: The choice of the material for plugging a dehiscence of the superior semicircular canal is based on the ease of use and the success of the procedure to permanently relieve symptoms without adverse side effects. Background: Dehiscence of the superior semicircular canal can lead to autophony, conductive hearing loss, and vertigo. Surgical treatment by plugging the canal is a highly effective treatment of the symptoms in many patients, although, the procedure can be associated with some degree of hearing loss in more than or equal to 25% of the patients. The available data indicate that adverse effects may be more frequently observed with bone wax as compared with other materials. Methods: In the present study we compare the tissue reactions induced by plugging the superior semicircular canal with autologous bone pate/bone chips, muscle, fat, artificial bone wax, and teflon in the gerbil model in an attempt to identify the material leading to successful plugging with the least adverse tissue reactions. Results: Our data show that successful plugging was achieved in 100% of the ears by bone pate/bone chips, teflon, and bone wax while the success rate was significantly lower (<50%) following muscle and fat. The proportion of adverse tissue reactions was significantly more pronounced using bone wax as compared with teflon and bone pate/bone chips. Conclusion: The use of teflon or autologous bone as a material for plugging a dehiscent superior semicircular canal should be favored over bone wax, muscle, and fat.